SavannahMM
SavannahMM
01-12-2016
Mathematics
contestada
What is the answer and steps to -12(k+4)=60?
Respuesta :
kishonwinston
kishonwinston
01-12-2016
-12(k+4) = 60
-12k-48=60
-12k = 108
k = 108/-12
k = -9
Answer Link
Аноним
Аноним
01-12-2016
-12(k+4)=60
-12k - 48 = 60
add 48 to both sides
-12k - 48 + 48 = 60 +48
simplify
-12k = 108
divide both sides by -12
-12k/-12 = 108/-12
simplify
k = -9
Answer Link
VER TODAS LAS RESPUESTAS ( 98+ )
Otras preguntas
Gravitational force acts on two objects with which of the following? A. mass B. force C. orbit D. speedI will thums up!!!
Which event led most directly to a decline in the political power of ancient Greek city-states in the Mediterranean Sea? A. Fighting between city-states led to
is it possible that the orientation of a figure could change after it has been translated? Explain.
this solid figure has three pairs of parallel faces and all faces are congruent
Give an example of a situation in which you would describe an object’s position in: a. one dimension b. two dimensions c. three dimensions
2x squared plus negative 5 - 10 equals zero
What is (10/3) squared?
How are ratios used in everyday life?
Define Popular Sovereignty.
Writing to explain if 5 potatoes together have a mass of 1 kilogram and 8 pears together have a mass of 1,200 grams, which has the great mass , a potato or a pe